2019
DOI: 10.1021/acs.jpcc.9b02354
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Charge Shift in Li+-Doped Giant Nested Fullerenes

Abstract: Over the last years, carbon nano-onions (CNOs) have been in focus in material science research.Their red-shifted absorption allows utilizing CNOs as promising photosensitizers. We report here a systematic study of excited state properties of six double-layered Li + doped fullerenes of Ih symmetry:[[Li@C240@C960] + and [Li@C540@C960] + . On the basis of TDDFT calculations, we show that the long-wave absorption by the Li + doped species leads to charge transfer (CT) between the inner and the outer shells unlike … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 50 publications
4
8
0
Order By: Relevance
“…The fact that the introduction of the positive charge does not affect the energy of LE states but strongly affects the CT states, clearly indicates the electrostatic nature of the observed effect. Such stabilization of CT state was previously reported for the experimentally and theoretically studied [10]CPP⊃Li + @C 60 complex, [10] as well as for Li + ‐doped carbon nano‐onions [13] and the Zn‐porphyrin–[10]CPP⊃C 60 junction [14] . An important point is that excited states with a high oscillator strength are found in each system.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…The fact that the introduction of the positive charge does not affect the energy of LE states but strongly affects the CT states, clearly indicates the electrostatic nature of the observed effect. Such stabilization of CT state was previously reported for the experimentally and theoretically studied [10]CPP⊃Li + @C 60 complex, [10] as well as for Li + ‐doped carbon nano‐onions [13] and the Zn‐porphyrin–[10]CPP⊃C 60 junction [14] . An important point is that excited states with a high oscillator strength are found in each system.…”
Section: Resultssupporting
confidence: 68%
“…complex, [10] as well as for Li + -doped carbon nano-onions [13] and the Zn-porphyrin- [10]CPP�C 60 junction. [14] An important point is that excited states with a high oscillator strength are found in each system.…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
“…The calculated E int values of the other force fields are considerably overestimated. It should be pointed out that the interactions energy estimated by ReaxFF force fields not only agrees with the DFT calculation by Hashmi and Lein [33] but also agrees well with Stasyuk et al [32] and Casella et al [31] where they used different DFT functionals. Finally, we note, with the exception of the original Tersoff and REBO-II force fields, all the considered force fields show similar trends in the interaction energies to the DFT results.…”
Section: Resultssupporting
confidence: 85%
“…A number of density functional theory (DFT) studies have explored the formation and interaction energies in carbon onions. [25][26][27][28][29][30][31][32][33] However, due to the computational cost associated with DFT methods, these studies have been limited to systems with hundreds of carbons. Molecular mechanics, on the other hand, is computationally much more economical and is routinely used for calculating structural properties of nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of Li + ‐encapsulated double‐shell CNOs has been recently studied in CT processes . It has been found that depending on the size of the inner and outer‐shells two types of CT states can be generated, namely, one with alternating charges like Li + @C 60 − @C 240 + and another with a positive charge on the outer shell as in Li@C 240 @C 540 + .…”
Section: Figurementioning
confidence: 99%